UTILIZING PICTURES IN INCREASING PUPILS’ VOCABULARY MASTERY IN AN EFL CLASS IN PALU CITY INDONESIA - Marzuki, Abdul Gafur (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
This research aimed at analyzing the implementation of pictures technique in increasing vocabulary of the fourth gradepupils of SDN 6 Palu. This research employed a collaborativeclassroom action research design and was implemented in the formof cycles consisting of four major steps: planning, implementing,observing and reflecting. The subject of the research were 34 pupilsof grade four B at SDN 6 Palu. The instruments used to collect datawere test, observation checklists, field notes, and questionnaire. Thisresearch was completed in two cycles because the results of theresearch in the first cycle did not meet the criteria of success. Eachof cycle comprises four meetings. The findings of the researchshowed that the applying of technique in teaching English canincrease pupils’ vocabulary mastery. This is shown by theimprovement of the mean score made by the pupils, that is: 7.04 incycle I to 8.10 in Cycle II and the number of the pupils who gotscores at least 6.5 or greater was 22 (64.71%) in cycle I to 34(100%) in cycle II. In addition, the pupils gave positive responsetoward the model applied as reflected from the results of threevariables of measurement of the questionnaire given: learningmotivation, learning result, and tasks accomplishment. It can beconcluded that the pictures technique is effective and applicable inteaching vocabulary.